Analysis of SIRT1 Expression in Plasma and in an in Vitro Model of Preeclampsia - Viana-Mattioli, Sarah [UNESP]; Nunes, Priscila [UNESP]; Cavalli, Ricardo; Sandrim, Valeria [UNESP] (Hindawi, 2020)
Preeclampsia (PE) is a pregnancy-specific disorder that affects 3-8% expecting mothers worldwide being one of the main causes of maternal and fetal morbidity and mortality. The search for altered circulating molecules in PE is an important target to better understand the pathophysiology of this disease. Therefore, we evaluated Sirtuin-1 (SIRT1) concentration in plasma from healthy pregnant (HP) women, gestational hypertensive women (GH), and preeclampsia women (PE) via enzyme-linked immunosorbent assay (ELISA). We also measured intracellular SIRT1 in HUVECs incubated with plasma from PE patients compared to HP and GH via Western Blot Assay. Statistical differences were considered when p<0.05. SIRT1 was downregulated in PE compared to HP and GH, both in plasma and in in vitro assay. Similarly, SIRT1 was also reduced in pregnant women who subsequently developed PE (case) compared to women who had healthy pregnancies (control). This reduction may be indicative of possible underlying pathophysiology mechanisms in PE.